(untitled) (Homoeopathy for All, 2025)
Academic research is fundamental to the progression of medical sciences, including homoeopathy. Despite its recognized importance, homoeopathic institutions encounter distinctive challenges that impede the cultivation of a robust research culture. This paper systematically analyzes the barriers faced by academic researchers in homoeopathic institutions, categorizing them into institutional, regulatory, infrastructural, and personal domains. Key barriers include lack of strategic vision, insufficient faculty training, limited funding, restricted data access, and inadequate research incentives. Recommendations are proposed to address these challenges and foster an environment conducive to high-quality scientific inquiry and innovation. A comprehensive multi-tiered approach is essential to promote scientific rigor and innovation in homoeopathic academia.